THE PROBLEM OF TERRITORIAL ZONING OF THE RUSSIAN FEDERATION: DOMESTIC AND INTERNATIONAL ASPECTS - V. A. Gorbanyov; B. I. Kochurov (Vestnik MGIMO-Universiteta)
The current economic regions in Russia were zoned in the 20-30s of the last century by the soviet State Planning Committee. Back then they played an outstanding role in economic development. However, today they do not correspond to the contemporary Russian realities of market economy.We tried to identify new regions, considering natural, economic, social, geo-ecological conditions. Therefore, the identified regions have a complex geographical nature. We carved out ten such regions: Stolichny, Central, European North, European South, North Caucasian, Uralo-Povolzhsky, West Siberian, North Siberian, South Siberian and Far Eastern.The authors collected statistical information of land area, population size and density, physical and geographical conditions, natural resources and economic activities for each district. Using the data, they identified for each region the natural population dynamics, the share of the population below the poverty line, the gross regional product, its structure, the supply of arable land, the rank of the geo-ecological tension, the balance of direct foreign investments and a number of other indicators. In particular the discrepancy between the area and the population in each region is shown. All regions are very different. While in European regions the share of the population is much larger than the share of area, in the Asian regions the situation is reversed: a very small proportion live on enormous area.In the era of globalization, it is important to consider transboundary fluxes of population and environmental pressure. We analyzed the immigration potential and environmental externalities of neighboring countries for the identified regions of Russia. It is shown that Ukraine, Kazakhstan and China represent the greatest environmental danger for Russia.Efficient geographical zoning is a necessary condition for improving the regional economy, and ultimately ensuring national security of the country.